Coefficient of friction and height loss: two criteria used to determine the mechanical property and stability of regenerated versus natural articular cartilage - Schwarz, Markus; Reisig, Gregor; Schneider-Wald, Barbara Katharina; Weiß, Christel; Hauk, Luisa; Schütte, Andy (Biomedicines, 2022)
Background: The coefficient of friction (CoF) serves as an indicator for the mechanical properties of natural and regenerated articular cartilage (AC). After tribological exposure, a height loss (HL) of the cartilage pair specimens can be measured. Our aim was to determine the CoF and HL of regenerated AC tissue and compare them with those of natural AC from non-operated joints and AC from joints where the regenerated tissues had been created after different treatments. Methods: In partial-thickness defects of the trochleae of the stifle joints of 60 Göttingen Minipigs, regenerated AC was created. In total, 40 animals received a Col I matrix, 20 laden with autologous chondrocytes, and 20 without. The defects of 20 animals were left empty. The healing periods were 24 and 48 weeks. A total of 10 not-operated animals, delivered the “external” control specimens. Osteochondral pins were harvested from defect and non-defect areas, the latter serving as “internal” controls. Using a pin-on-plate tribometer, we measured the CoF and the HL. Results: The CoF of the regenerated AC ranged from 0.039 to 0.069, and the HL, from 0.22 mm to 0.33 mm. The differences between the regenerated AC of the six groups and the “external” controls were significant. The comparison with the “internal” controls revealed four significant differences for the CoF and one for the HL in the operated groups. No differences were seen within the operated groups. Conclusions: The mechanical quality of the regenerated AC tissue showed inferior behavior with regard to the CoF and HL in comparison with natural AC. The comparison of regenerated AC tissue with AC from untreated joints was more promising than with AC from the treated joints.
Gesehen am 25.07.2023